Chromogranin A Detection in Saliva of Type 2 Diabetes Patients - Martine Soell; Ahmed Feki; Matthias Hannig; Hidehiko Sano; Michel Pinget; Denis Selimović (Biomolecules & Biomedicine, 2010)
Chromogranin A is present in secretion granules of nerve, endocrine and immune cells and is a precursor of several peptides with antibacterial and antifungal properties at micromolar concentrations.